Drosophila as a Model to Study Cellular Communication Between the Hematopoietic Niche and Blood Progenitors Under Homeostatic Conditions and in Response to an Immune Stress - Morin-Poulard, Ismaël; Tian, Yushun; Vanzo, Nathalie; Crozatier, Michèle (Frontiers in Immunology, 2021)
In adult mammals, blood cells are formed from hematopoietic stem progenitor cells, which are controlled by a complex cellular microenvironment called “niche”. Drosophila melanogaster is a powerful model organism to decipher the mechanisms controlling hematopoiesis, due both to its limited number of blood cell lineages and to the conservation of genes and signaling pathways throughout bilaterian evolution. Insect blood cells or hemocytes are similar to the mammalian myeloid lineage that ensures innate immunity functions. Like in vertebrates, two waves of hematopoiesis occur in Drosophila. The first wave takes place during embryogenesis. The second wave occurs at larval stages, where two distinct hematopoietic sites are identified: subcuticular hematopoietic pockets and a specialized hematopoietic organ called the lymph gland. In both sites, hematopoiesis is regulated by distinct niches. In hematopoietic pockets, sensory neurons of the peripheral nervous system provide a microenvironment that promotes embryonic hemocyte expansion and differentiation. In the lymph gland blood cells are produced from hematopoietic progenitors. A small cluster of cells called Posterior Signaling Centre (PSC) and the vascular system, along which the lymph gland develops, act collectively as a niche, under homeostatic conditions, to control the balance between maintenance and differentiation of lymph gland progenitors. In response to an immune stress such as wasp parasitism, lymph gland hematopoiesis is drastically modified and shifts towards emergency hematopoiesis, leading to increased progenitor proliferation and their differentiation into lamellocyte, a specific blood cell type which will neutralize the parasite. The PSC is essential to control this emergency response. In this review, we summarize Drosophila cellular and molecular mechanisms involved in the communication between the niche and hematopoietic progenitors, both under homeostatic and stress conditions. Finally, we discuss similarities between mechanisms by which niches regulate hematopoietic stem /progenitor cells in Drosophila and mammals.